Novel methyl substituted 1-(5, 6-dihydro-[1, 2, 4]triazolo[4, 3-a]pyrazin-7(8H)-yl)methanones are P2X7 antagonists. Issue 16 (15th August 2015) - Rudolph, Dale A.; Alcazar, Jesus; Ameriks, Michael K.; Anton, Ana Belen; Ao, Hong; Bonaventure, Pascal; Carruthers, Nicholas I.; Chrovian, Christa C.; De Angelis, Meri; Lord, Brian; Rech, Jason C.; Wang, Qi; et al.
Graphical abstract: Abstract: The optimization efforts that led to a novel series of methyl substituted 1-(5, 6-dihydro-[1, 2, 4]triazolo[4, 3- a ]pyrazin-7(8 H )-yl)methanones that are potent rat and human P2X7 antagonists are described. These efforts resulted in the discovery of compounds with good drug-like properties that are capable of high P2X7 receptor occupancy in rat following oral administration, including compounds7n (P2X7 IC50 = 7.7 nM) and7u (P2X7 IC50 = 7.7 nM). These compounds are expected to be useful tools for characterizing the effects of P2X7 antagonism in models of depression and epilepsy, and several of the compounds prepared are candidates for effective P2X7 PET tracers.